PENGARUH HAND MASSAGE TERHADAP PENURUNAN TINGKAT KECEMASAN KLIEN PRE OPERASI DI RUMAH SAKIT PATAR ASIH LUBUK PAKAM TAHUN 2021 - Dian Anggri Yanti; Pitriani .; Leni Sumiati Silaban; Scolastika Purba; Juni Mariati Simarmata (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2021)
The number of patients with surgery has increased significantly from year to year. Recorded in 2011 there were 140 million patients in all hospitals in the world, Anxiety is a common thing in patients who are going to undergo surgery. Anxiety that occurs with preoperative patients can be felt since the start of being scheduled for surgery until the time for surgery arrives and hand massage can be useful to reduce pain because it has a relaxing effect and reduces anxiety. Purpose: to determine the effect of hand massage on the reduction of preoperative client anxiety levels at Patar Asih Lubuk Pakam Hospital in 2021. Method: Pre-experimental design with one-group pre-post test design. The research subjects were preoperative inpatients. Population: preoperative patients in Galilee inpatient room. Sample: purposive sampling. Results: After the hand massage treatment, the level of anxiety in the treatment group decreased significantly, while the control group did not experience a significant decrease. In the control group the pre-test average was 19.63, while the post-test average was 19.06, this indicates a very small decrease so that the decrease was not significant. In the treatment group the average before treatment was 19.94 after treatment decreased to 16.19. Conclusion: The results of hypothesis testing (p <0.05) prove that hand massage significantly reduces anxiety levels before surgery.